Transcriptional Activity of the Bacterial Replication Initiator DnaA - Menikpurage, Inoka P.; Woo, Kristin; Mera, Paola E. (Frontiers in Microbiology, 2021)
In bacteria, DnaA is the most conserved DNA replication initiator protein. DnaA is a DNA binding protein that is part of the AAA+ ATPase family. In addition to initiating chromosome replication, DnaA can also function as a transcription factor either as an activator or repressor. The first gene identified to be regulated by DnaA at the transcriptional levels was dnaA. DnaA has been shown to regulate genes involved in a variety of cellular events including those that trigger sporulation, DNA repair, and cell cycle regulation. DnaA’s dual functions (replication initiator and transcription factor) is a potential mechanism for DnaA to temporally coordinate diverse cellular events with the onset of chromosome replication. This strategy of using chromosome replication initiator proteins as regulators of gene expression has also been observed in archaea and eukaryotes. In this mini review, we focus on our current understanding of DnaA’s transcriptional activity in various bacterial species.